Incidence of retinal changes in pregnant women due to pregnancy induced hypertension and its correlation with clinical profile - Rai, Himanshy; Rahman, Zakia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy induced hypertension (PIH) is associated with many other pathological complications. Pathological changes of this disease appear to be related to vascular endothelial dysfunction and its consequences. One such complication or effect of PIH is retinal changes. Methods: This observational study was conducted of 110 cases over a period of 12 months from March 2018 to February 2019 in department of obstetrics of gynecology in Kamla Raja Hospital, G. R. Medical College, Gwalior, Madhya Pradesh. All the patients who fulfilled the diagnostic criteria of PIH admitted in the obstetric ward. Results: Retinopathic changes were noted in 36.36% out of which grade I, grade II, grade III and grade IV have 11.82%, 8.18%, 10.19% and 5.45% cases respectively. In + proteinuria 10.9% of cases have positive findings, in ++ proteinuria 18.18% cases have positive findings, in +++ 7.27% cases have retinopathy but severity increases with a grade of proteinuria. 40% cases retinopathic changes of mild preeclampsia have positive finding, 36.36% in severe preeclampsia and 23.64% in cases of eclampsia. As overall severity of PIH increases retinopathies in patients increases. Conclusions: Visual symptoms are few in patients with PIH and often absent unless the macula is involved. Sudden onset of headache, which is resistant to routine therapy in these patients, may be the warning symptom before the onset of first convulsion. By repeated fundus examinations at regular intervals one can assess the severity of the disease and also response to treatment instituted.